Photometric metallicities in Boötes I. Issue 1 (4th February 2014) - Hughes, J.; Wallerstein, G.; Dotter, A.; Geisler, D.
Abstract: We present new Strömgren and Washington data sets for the Boötes I dwarf galaxy, and combine them with the available Sloan Digital Sky Survey photometry. The goal of this project is to refine a ground-based, practical, accurate method to determine age and metallicity for individual stars in Boötes I that can be selected in an unbiased imaging survey, without having to take spectra. With few bright upper red giant branch stars and distances of about 35–250 kpc, the ultra-faint dwarf galaxies (UDFs) present observational challenges in characterizing their stellar population. Other recent studies have produced spectra and proper motions, making Boötes I an ideal test case for our photometric methods. We produce photometric metallicities from Strömgren and Washington photometry, for stellar systems with a range of −1.0 > [Fe/H] > −3.5. Needing to avoid the collapse of the metallicity sensitivity of the Strömgren m 1 -index on the lower red giant branch, we replace the Strömgren v filter with the broader Washington C filter to minimize observing time. We construct two indices: m *  = ( C  −  T 1 )0  − ( T 1  −  T 2 )0 and m **  = ( C  −  b )0  − ( b  −  y )0 . We find that CT 1 by is the most successful filter combination, for individual stars with [Fe/H] < −2.0, to maintain ∼0.2 dex [Fe/H]-resolution over the whole red giant branch. The m ** -index would be the best choice for space-based observations because the ( C  −  y ) colour is not sufficient to fix metallicity alone in an understudied system. Our photometric metallicites of stars in the central regions of Boötes I confirm that there is a metallicity spread of at least −1.9 > [Fe/H] > −3.7. The best-fitting Dartmouth isochrones give a mean age, for all the Boötes I stars in our data set, of 11.5 ± 0.4 Gyr. From ground-based telescopes, we show that the optimal filter combination is CT 1 by, avoiding the v filter entirely. We demonstrate that we can break the isochrones' age–metallicity degeneracy with the CT 1 by filters, using stars with log  g  = 2.5 − 3.0, which have less than a 2 per cent change in their ( C  −  T 1 ) colour due to age, over a range of 10–14 Gyr.